Ray Hitt reading Hitt Fireworks brochure, Seattle, December 1979 - Law, Denis (1979)
Ray's father T.G. Hitt started the Hitt Fireworks Company. Ray followed in his father's footsteps with his interest in chemistry and fireworks experimentation and innovation. Brochure reads: Hitt Fireworks Company, 5234 37th Avenue South, Seattle, Washington. Phone RAinier 0360. Cable Address: Hittpyro. Hitt Fireworks Company, Manufacturers of Everything in Fireworks Since 1898. Hitt's Flashcrackas. A Reg'lar Feller. Write for Complete Illustrated Programs for Display Exhibition Fireworks. Contractors to Major Fairs and Expositions, Including Two Grand Prizes. Alaska-Yukon Pacific Exposition, Seattle, Wash. Over 150 Displays, Medal of Honor, Official Pyrotechnists to Panama Pacific International Exposition, San Francisco, 1915. Pyrotechnists to Philadelphia, Sequi-Centennial Exposition, 1926. We Can Supply You With the Above Poster for Your Stand. From Coast to Coast - The Choice of Young America. Season 1938. Commercial Fireworks Price List. Subject to Dealer's Discount. Buy Direct from Manufacturer. The Following Firms Sell Our Products: Hitt Flashcracka Company, Seattle, Washington; Hitt Fireworks Company of Oregon, The J.K. Gill Company, 408 SW Fifth, Portland, Oregon; Pacific States Fireworks Company, Los Gatos, Calif.; Pacific States-Hitt Fireworks Company, 516 Lankershim Bldg., Los Angeles, Calif. Buy Hitt Fireworks for the 4th. All Goods Sold on Non-Consignment Basis. A Pacific Coast Payroll Employing All American Workers. Thirty Years Consistent Fireworks Manufacture Since 1898 - Fifty Patents. Label on verso: Photo by Denis Law, Puget Sound Publishing Co., Renton Reporter - Kent Reporter - Auburn Reporter. Caption taken from RVHS records.